Analisis Tipologi dan Ketimpangan Pembangunan Ekonomi Antar Wilayah di Provinsi Papua Barat - Arqilaus A. V. Homer; Charley M. Bisai (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2024)
This study aims to analyze the regional typology and measure the level of economic development inequality among districts and cities in West Papua Province. The research period covers 2017 to 2021 for inequality analysis and 2018 to 2021 for typology analysis. The analytical methods used are the Williamson Index to measure the level of development inequality, and the Klassen Typology to classify regions based on patterns and structures of economic growth. Both methods were applied to two scenarios, namely GRDP with the oil and gas sector and GRDP without the oil and gas sector, in order to examine the differential impact of the oil and gas sector on inequality and regional classification. The results show that the level of inequality in West Papua Province is classified as severe for GRDP including oil and gas, with an average Williamson Index of 1.51428, while for GRDP excluding oil and gas, the inequality is classified as moderate, with an average of 0.4327. This inequality is caused by the concentration of economic activities in certain regions such as Teluk Bintuni Regency, Sorong Regency, and Sorong City, as well as differences in natural resources and infrastructure among regions. Based on the Klassen Typology analysis for GRDP including oil and gas, no region falls into quadrant I (advanced and fast-growing regions). Sorong Selatan, Maybrat, and Pegunungan Arfak Regencies are in quadrant II (advanced but depressed regions), Teluk Bintuni and Sorong Regencies are in quadrant III (fast-growing but not advanced regions), and seven other regions are in quadrant IV (relatively lagging regions). Meanwhile, for GRDP excluding oil and gas, Teluk Bintuni and Raja Ampat Regencies fall into quadrant I, seven regions are in quadrant III, and four regions are in quadrant IV. The discussion confirms that the oil and gas sector has a dominant influence on the regional economy, so that good management of this sector can reduce inequality, whereas poor management will widen the gap. This study recommends policy prioritization for lagging regions such as Pegunungan Arfak, Tambrauw, and Maybrat, as well as more equitable distribution of economic concentration and infrastructure development throughout West Papua Province. Keywords: Klassen Typology, Williamson Index, development inequality, West Papua, oil and gas